2015
DOI: 10.1186/s13012-015-0369-z
|View full text |Cite
|
Sign up to set email alerts
|

Reporting standards for guideline-based performance measures

Abstract: BackgroundThe Guidelines International Network (G-I-N) aims to promote high quality clinical guideline development and implementation. Guideline-based performance measures are a key implementation tool and are widely used internationally for quality improvement, quality assurance, and pay for performance in health care. There is, however, no international consensus on best methods for guideline-based performance measures. In order to address this issue, the G-I-N Performance Measures Working Group aimed to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 45 publications
0
60
0
1
Order By: Relevance
“…We added articles cited by the initial list, until this ceased to yield further candidate features. The final list of articles reviewed comprised 22 journal articles [4,7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and 17 reports and textbooks [10][11][12][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Stage 1: Identifying the Candidate Features To Include In Thmentioning
confidence: 99%
“…We added articles cited by the initial list, until this ceased to yield further candidate features. The final list of articles reviewed comprised 22 journal articles [4,7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and 17 reports and textbooks [10][11][12][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Stage 1: Identifying the Candidate Features To Include In Thmentioning
confidence: 99%
“…A study by Grilli et al 17 analyzed 431 guidelines developed by professional societies from 1988 to 1998 and found that only 12% provided information on the levels of evidence and grading of recommendations. Some recent studies 53 , a few conducted in countries such as Korea 13 and Brazil 21 , also identified shortcomings in the guideline development process as one of the aspects that most contributed to the low quality of guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Additional methodological expertise may be required for conducting these steps. Adequate methodology should be used to develop quality indicators that are valid and reliable for evaluating the quality of healthcare [24].…”
Section: Phase 3: Developing a Quality Indicatormentioning
confidence: 99%
“…A quality indicator can be used for monitoring healthcare and to consequently assess changes in clinical practice [24]. Preferably, quality indicators are applicable to large groups of patients and are able to show 3e Determine feasibility, interpretability and acceptability of the PROM Feasibility is related to various aspects such as the time of administration (number of items), availability of translated version, and costs for using the PROM; interpretability is related to meaningful use of the scores on the PROM such as minimal clinical important difference; acceptability is related to support of patients and clinicians in using the PROM 3f Select suitable PROM(s) Selection of the PROM(s) based on the outcomes of step 3d and 3e, for which formal and informal consensus procedures can be used.…”
Section: Phase 3: Developing a Quality Indicatormentioning
confidence: 99%